Islamic economic framework for the exercise of Islamic financial activities: its conformity with Maqasid al-Shari'ah - Habibullah, Mohammad; Al Faruque, Abdullah; Faruque, Md. Omar; Atiullah, Md (IIUM Press, 2023)
With the establishment of Islamic banks throughout the latter half of the 20th century, Islamic finance became institutionalized. The emergence of new Islamic banks was accompanied by the emergence of Islamic insurance firms and other Islamic financial organizations. The Maqasid al Shari’ah in financial transactions reveals the overarching goals and significance to which it aspires through decision-making. It is clear from the careful and continuous examination of several Qur'anic verses and the Prophet's (PBUH) Sunnah regarding financial matters that the Shari'ah has adhered to specific objectives in formulating its financial laws and regulations. These objectives include the fair distribution of wealth within society, continual wealth investments, the satisfaction of economic prosperity for all through the satisfaction of basic human needs, the openness of financial transactions to avoid disputes, and the legitimacy of ownership of private and public wealth. The study offers a Maqasid-based development paradigm, which views development from the perspective of extracting benefit and removing harm. This calls for fostering things that make life simpler, more meaningful, and prosperous while preventing all causes of harm, socioeconomic hardship, and underdevelopment. The approach's strength lies in the proper weight it accords to morality, spirituality, and faith as catalysts for prolonged moderate growth and in its emphasis on all-encompassing yet restrained material progress. The study argues for a detailed investigation of the economic growth and the science of Maqasid al-Shari'ah. The qualitative method is applied in this study to evaluate the fundamental concept of Maqasid Al-Shariah from the primary and secondary sources of knowledge in Islam, which shows the model of the economic system to identify the challenges of governing the Islamic banks and Islamic financial activities accordingly.